Mercury Content in Three Edible Wild-Growing Mushroom Species from Different Environmentally Loaded Areas in Slovakia: An Ecological and Human Health Risk Assessment - Lenka Demková; Július Árvay; Martin Hauptvogl; Jana Michalková; Marek Šnirc; Ľuboš Harangozo; Lenka Bobuľská; Daniel Bajčan; Vladimír Kunca (Journal of Fungi, 2021)
Three edible mushroom species (Imlera badia, Boletus subtomentosus, Xerocomellus chrysenteron) sampled in 60 different localities of Slovakia were evaluated to determine health risks (associated with mercury content) arising from their consumption. Total content of mercury in soil and mushroom samples was determined by an AMA-254 analyzer. Soil pollution by mercury was evaluated by contamination factor (Cf), pollution load index (PLI), and geoaccumulation index (Igeo). Bioaccumulation factor (BAF), translocation factor (Qc/s), provisional tolerably weekly intake (%PTWI), estimated daily intake (EDI), and target hazard quotient (THQ) were used to describe and compare uptake and transition abilities of mushrooms, and the health risk arising from mushroom consumption. Mercury content in soil significantly influences the content of mercury in mushroom fruiting body parts. Caps and stipes of Boletus subtomentosus were found to be the best mercury accumulator. According to the EDI, consumption of the evaluated mushroom species represents a serious threat for adults and children. The lowest values of THQ were found for Xerocomellus chysenteron.